2015
DOI: 10.15171/ijoem.2015.436
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neuron-Specific Enolase, Biogenic Amino-Acids and Neurobehavioral Function in Lead-Exposed Workers from Lead-Acid Battery Manufacturing Process

Abstract: Serum NSE cannot be used as a marker for BLL. The only domain of neurobehavioral function tests that is affected by increased BLL in workers of lead-acid battery manufacturing process is that of the "attention and perception" (SDST).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…In this study, no significant relationship was observed between age and blood lead and this could be attributed to the younger age of the studied subjects. However, in the study of Ravibabu et al, a significant relationship was found between age and serum levels (14). The present investigations showed a positive correlation between blood lead levels and years of employment and also a lower score of the Benton Visual Test.…”
Section: Discussioncontrasting
confidence: 51%
“…In this study, no significant relationship was observed between age and blood lead and this could be attributed to the younger age of the studied subjects. However, in the study of Ravibabu et al, a significant relationship was found between age and serum levels (14). The present investigations showed a positive correlation between blood lead levels and years of employment and also a lower score of the Benton Visual Test.…”
Section: Discussioncontrasting
confidence: 51%
“…It has highly toxic effects on all mammals. Many reports have shown the toxic effects of lead on bone, hematopoiesis, and renal function, and on the digestive, immune and nervous systems (Gurer-Orhan et al 2004;Ekong et al 2006;Ravibabu et al 2015). Additionally, lead preferentially accumulates in male reproductive organs and leads to adverse effects on the male reproductive system (Benoff et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“… 1 Occupational exposure to lead occurs through inhalation and ingestion. Recent studies on lead-battery manufacturing workers have reported high musculoskeletal disorders with markers of inflammation, 2 mucocutaneous changes, 3 oxidative stress, 4 altered serum magnesium fractions, 5 elevated blood lead levels (BLLs), 6 , 7 reticulocytosis, 8 altered genetic polymorphisms of δ-aminolevulinic acid dehydratase (ALAD), 9 impaired biogenic amino acids with neurobehavioral function, 10 genotoxicity, 11 impaired coagulation function, 12 health problems, 13 , 14 male reproductive function, 15 ocular changes, 16 impaired hematological parameters, 17 and altered calcium metabolism by inhibiting the kidney 1-𝛼-hydroxylase enzyme, which is required for 1, 25 dihydroxy-vitamin D 3 synthesis 18 .…”
Section: Introductionmentioning
confidence: 99%